2020
DOI: 10.3350/cmh.2019.0074
|View full text |Cite
|
Sign up to set email alerts
|

Limited expression of TLR9 on T cells and its functional consequences in patients with nonalcoholic fatty liver disease

Abstract: Background/Aims: Toll-like receptors (TLRs) modulate T cell responses in diverse diseases. Co-stimulation of T cell activation via TLR9 induces production of interferon gamma (IFN-γ), priming of which is critical for differentiation of pro-inflammatory macrophages. These macrophages have a crucial role in nonalcoholic fatty liver disease (NAFLD). We aimed to evaluate the expression of TLR9 protein on T cells and the consequences of TLR9-mediated triggering of these cells in patients with NAFLD.Methods: Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Instead of investigating a loss-of-function population, Alegre et al took the approach of identifying patients with matched parameters of metabolic dysfunction (including BMI, HOMA-IR, lipids), but who were diagnosed by biopsy with either simple steatosis or NASH (166). They focused on TLR9 expression in T cells, as intrahepatic T cells' role in NASH progression was confirmed in several studies.…”
Section: Evidence Of Tlr9 Activation and Integral Involvement In Humamentioning
confidence: 99%
“…Instead of investigating a loss-of-function population, Alegre et al took the approach of identifying patients with matched parameters of metabolic dysfunction (including BMI, HOMA-IR, lipids), but who were diagnosed by biopsy with either simple steatosis or NASH (166). They focused on TLR9 expression in T cells, as intrahepatic T cells' role in NASH progression was confirmed in several studies.…”
Section: Evidence Of Tlr9 Activation and Integral Involvement In Humamentioning
confidence: 99%
“…Dear Editor, I recently read an interesting article by Alejandra et al 1 which showed the relationship between toll-like receptor 9 (TLR9), cluster of differentiation 69 (CD69) expression, and interferon-γ expression related to liver injury in patients with nonalcoholic fatty liver disease. Non-alcoholic fatty liver disease involves a comprehensive process from simple fatty liver to nonalcoholic steatohepatitis (NASH), which includes hepatocellular damage (hepatocyte ballooning) due to infiltration of inflammatory cells as well as fat accumulation, which thereby progresses to NASH-associated fibrosis and NASH-associated cirrhosis.…”
mentioning
confidence: 99%
“…I have briefly summarized the results, as shown in the table below, to enhance the readers' understanding ( Table 1). 1 First, the authors analyzed TLR9 expressions in both intrahepatic and peripheral CD4 T and CD8 T cells. However, only peripheral blood mononuclear cells were used to examine the expressions of CD69 or interferon-γ.…”
mentioning
confidence: 99%
“…Dear Editor, I read the original article titled "Limited expression of TLR9 on T cells and its functional consequences in patients with nonalcoholic fatty liver disease" by Alegre et al 1 with great interest. This article studied the role of toll-like receptor (TLR) 9 on T cells in patients with nonalcoholic fatty liver disease (NAFLD) and found positive associations between TLR9 expressions on intrahepatic CD4 + T cells, necroinflammation, and liver fibrosis.…”
mentioning
confidence: 99%